Novel prehospital lactate cut-off estimation for mortality: a multicentre observational study - Ancor Sanz-García; Carlos del Pozo Vegas; Daniel Zalama-Sánchez; Raúl López-Izquierdo; Francisco Martín-Rodríguez; Pedro Ángel de Santos Castro; Eduardo Silva Alvarado; Santos Gracia Villar; Luis Alonso Dzul López; Silvia Aparicio Obregón; Rubén Calderon Iglesias (BMJ Open)
Objectives Point-of-care testing available in prehospital settings requires the establishment of new medical decision points. The aim of the present work was to determine the cut-off of the lactate threshold that activates alert triggers for all-cause 2-day mortality.Design Multicentre, prospective, ambulance-based, observational study.Setting Patients treated via emergency medical services (EMSs) and delivered to the emergency department between 2019 and 2023 were selected in Spain.Participants Adults with any acute disease.Primary and secondary outcome measures Epidemiological data, vital signs and prehospital point-of-care glucose and lactate levels were obtained. The outcome was all-cause 2-day in-hospital mortality. The cut-offs were obtained via three different methods: (i) indirect (which considers survivors and non-survivors), direct (which considers only survivors) assessment and lactate quartile. Additionally, the quartile approach was used to determine the differences in lactate distribution between survivors and non-survivors. Three different back-to-back studies with the same methodology were used.Results A total of 11 713 patients fulfilled the inclusion criteria. The mortality rate was 4.6% (542 patients). The difference in the median prehospital lactate concentration (mmol/L) between survivors and non-survivors was statistically significant (p<0.001): 2.29 (95% CI 1.43 to 3.38) and 7.14 (95% CI 5.11 to 9.71), respectively. Globally, the cut-off for all the studies combined was estimated by the direct method to be 3.71 mmol/L (95% CI 2.92 to 3.91), which was similar to the indirect value of 3.07 (95% CI 2.95 to 5.49) and the third quartile of 4.00. The mortality rate in patients who were less than 3.71 mmol/L was 0.004%, and that above that cut-off was 18%.Conclusions This study established a real-world lactate cut-off for 2-day in-hospital mortality of 3.71 mmol/L (95% CI 2.92 to 3.91) on the basis of data from the EMS. Considering this cut-off point could improve patient management via EMS services, allowing quick identification of patients at high risk of clinical worsening.Trial registration number ISRCTN Registry (ISRCTN17676798, ISRCTN48326533, ISRCTN49321933).